Review of the deep-water asellote genus Notopais Hodgson, 1910 (Crustacea: Isopoda: Munnopsididae) with description of three new species from the south-western Pacific - Merrin, Kelly L. (Zootaxa, 2004)
The munnopsidid genus Notopais Hodgson, 1910 is taken out of synonymy with Echinozone Sars, 1897. The type species Notopais spicata Hodgson, 1910 and Notopais quadrispinosa (Beddard, 1886) are redescribed and three new species described: Notopais beddardi n. sp. collected from Antarctica at a depth of less than 37 metres; Notopais minya n. sp. collected from the south-eastern Australian continental slope between the depths of 429 466 metres; and Notopais zealandica n. sp. collected from the Chatham Rise between the depths of 1386 1640 metres, off the south-eastern New Zealand coast. Notopais is distinguished from Echinozone by three defining characters: the flattened appearance of the ventral side of the cephalon, the presence of pedestal setae on the pereonites and antenna 2 article 1 with produced distolateral angle with prominent spine and distal robust seta. This genus is exclusively found in the Southern Hemisphere and is known from Antarctica and the south-western Pacific.